2013
DOI: 10.1017/s1479262113000014
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of cassava (Manihot esculentaCrantz) landraces and cultivars from southern, eastern and central Africa

Abstract: Studies to quantify genetic variation in cassava germplasm, available within the national breeding programmes in Africa, have been limited. Here, we report on the nature and extent of genetic variation that exists within 1401 cassava varieties from seven countries: Tanzania (270 genotypes); Uganda (268); Kenya (234); Rwanda (184); Democratic Republic of Congo (DRC; 177); Madagascar (186); Mozambique (82). The vast majority of these genotypes do not exist within a formal germplasm conservation initiative and we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 35 publications
3
45
2
Order By: Relevance
“…The sequences obtained from each manioc landrace through its genetic analysis were read, organized and analyzed to obtain the genetic structure of the population of the samples collected. The genetic structure was obtained using a Bayesian model approach [81] with the STRUCTURE 2.2 software [82]. This Bayesian analysis determines the minimum number of populations (K) that could have generated the observed diversity using an admixture model and assumes that each individual inherited some portion of its ancestry from each one of the K populations determined.…”
Section: Discussionmentioning
confidence: 99%
“…The sequences obtained from each manioc landrace through its genetic analysis were read, organized and analyzed to obtain the genetic structure of the population of the samples collected. The genetic structure was obtained using a Bayesian model approach [81] with the STRUCTURE 2.2 software [82]. This Bayesian analysis determines the minimum number of populations (K) that could have generated the observed diversity using an admixture model and assumes that each individual inherited some portion of its ancestry from each one of the K populations determined.…”
Section: Discussionmentioning
confidence: 99%
“…The F 1 progeny were first screened to detect off types and selfs using 12 SSR markers (Kawuki et al, 2013) that were identified as being polymorphic between the two parents. Genotyping by sequencing (GBS) (Elshire et al, 2011) was performed on the confirmed progeny at the University of California, Berkeley (ICGMC, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Adult numbers were counted on three randomly selected sub-set of 10 plants per genotype, starting at 82 DAP and, thereafter, at 30 days for four consecutive periods; damage scores were recorded concurrently (Kawuki et al, 2013). Each leaf was held gently and turned upside down to facilitate counting of adult insects during the relatively cooler periods of the day (7.00 am to 10.00 am.)…”
Section: Methodsmentioning
confidence: 99%